Maternal Serum Ferritin, C-Reactive Protein, and Procalcitonin Levels for Predicting Subclinical Intra-Amniotic Infection in Preterm Premature Rupture of Membrane - Nahedh, Balsam N.; Shalal, Maad M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: The preterm premature rupture of the membrane is linked to various perinatal problems, including chorioamnionitis. Objectives: To evaluate the use of serum ferritin, C-reactive protein, and procalcitonin as early indicators for predictions of subclinical intra-amniotic fluid infection. Methods: A case-control study was conducted at Baghdad Teaching Hospital from January to October 2021. A convenient sample of 90 singleton pregnant women with a live fetus between 24 - 36 weeks of gestation were divided into three groups: Group 1 (controls) included 30 women with intact membranes and no signs of labour seen in the outpatient obstetrics clinic in Baghdad Teaching Hospital; Group 2 included 30 women with preterm premature rupture of membrane (PPROM) but without chorioamnionitis; and Group 3 included 30 women with PPROM and chorioamnionitis. The second and third groups were collected from the labour room in Baghdad Teaching Hospital. Results: There was no significant difference in the levels of C-reactive protein between the study groups. Serum ferritin and Procalcitonin levels were normal in all of the participants, with a significant difference in the level of Procalcitonin between group 2 (PPROM with chorioamnionitis) and group 3 (PPROM without chorioamnionitis). Conclusion: Procalcitonin might be used to detect the presence of chorioamnionitis. Serum ferritin and C-reactive protein had no role in the detection of chorioamnionitis among patients with preterm premature membrane rupture.